2019
DOI: 10.7554/elife.48750
|View full text |Cite
|
Sign up to set email alerts
|

A toolbox of nanobodies developed and validated for use as intrabodies and nanoscale immunolabels in mammalian brain neurons

Abstract: Nanobodies (nAbs) are small, minimal antibodies that have distinct attributes that make them uniquely suited for certain biomedical research, diagnostic and therapeutic applications. Prominent uses include as intracellular antibodies or intrabodies to bind and deliver cargo to specific proteins and/or subcellular sites within cells, and as nanoscale immunolabels for enhanced tissue penetration and improved spatial imaging resolution. Here, we report the generation and validation of nAbs against a set of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 70 publications
(93 reference statements)
1
53
0
4
Order By: Relevance
“…Exorbitant expression levels can be circumvented by a replacement strategy in which a tagged protein is expressed in a knock-down or knock-out background [9], but this will, at best, only approximate endogenous levels and is uncoupled from endogenous transcriptional or translational regulatory mechanisms. Recombinant antibody-based approaches have been developed for live-cell imaging of neuronal proteins, but they have so far been restricted to a few targets [10][11][12][13][14]. The generation of fluorescently tagged knock-ins (for instance, in mouse lines) prevents these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Exorbitant expression levels can be circumvented by a replacement strategy in which a tagged protein is expressed in a knock-down or knock-out background [9], but this will, at best, only approximate endogenous levels and is uncoupled from endogenous transcriptional or translational regulatory mechanisms. Recombinant antibody-based approaches have been developed for live-cell imaging of neuronal proteins, but they have so far been restricted to a few targets [10][11][12][13][14]. The generation of fluorescently tagged knock-ins (for instance, in mouse lines) prevents these issues.…”
Section: Introductionmentioning
confidence: 99%
“…The applications are multiple. For instance, fluorescent nanobodies can be expressed at a determined physiological phase of the host cells to follow the fate of the corresponding antigens without interfering with their activity and by such a way specifically labeling distinct antigens and subcellular regions [48]. The clear advantage of nanobodies over conventional antibodies is their structural simplicity with a single disulfide bond that in several cases is not obligatory for reaching stable Both heavy-and light-chain variable domains contribute to the antigen-selective binding surface of conventional IgGs, whereas the heavy-chain variable domain of Camelidae IgGs provides alone the complete epitope for the antigen specific recognition.…”
Section: How To Choose Between Mammalian and Bacterial Expression Sysmentioning
confidence: 99%
“…Gene therapy via the AAV-mediated delivery of an anti-Aβ42 intrabody in an AD mouse model allowed partial clearance of Aβ42 deposits [155], and in a follow-up study, myelin integrity was restored in mice treated with intrabody gene therapy [156]. An intrabody was furthermore used for imaging purposes in live neurons to study mechanisms of memory impairment in AD [157], and intrabodies have been found to be generally valuable tools for imaging purposes in neurons [158]. AD is also associated with abnormal tau phosphorylation as well as aggregation and is the most common tauopathy [159,160].…”
Section: Alzheimer's Diseasementioning
confidence: 99%